Coping processes and health-related quality of life in Parkinson’s disease - Bucks, R.; Cruise, K.; Skinner, T.; Loftus, Andrea; Barker, R.; Thomas, M. (Wiley Interscience, 2011)
Objective: This study investigated the predictive value of various coping processes for the psychologicaland disease specific aspects of health-related quality of life (HRQoL) in Parkinson’s disease (PD).Method: Cross-sectional study of 85 participants with PD using the Ways of Coping Questionnaire(WCQ), Depression, Anxiety, and Stress Scale (DASS-21), quality of life (PDQ-39), and sociodemographic and clinical variables.Results: Greater use of planful problem solving coping was found to be significantly associatedwith better HRQoL in relation to cognitive impairment, communication and bodily discomfort.In addition to greater disease duration, greater use of escape-avoidance coping processes wereidentified as significant predictors of poorer HRQoL outcomes in the domains of mood and emotionalwell-being.Conclusion: Psychological interventions such as mindfulness training, aimed at reducing the use ofescape-avoidance copying, may help to improve HRQoL in PD. Copyright# 2010 John Wiley & Sons,Ltd.